Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
a) Sửa đề
\(x^4+2x^3+x^2\)
\(=\left(x^4+x^3\right)+\left(x^3+x^2\right)\)
\(=x^3\left(x+1\right)+x^2\left(x+1\right)\)
\(=\left(x+1\right)\left(x^3+x^2\right)\)
\(=\left(x+1\right).x^2\left(x+1\right)\)
\(=x^2\left(x+1\right)^2\)
b) \(x^3-x+3x^2y+3xy^2+y^3-y\)
\(=\left(x^3+3x^2y+3xy^2+y^3\right)-\left(x+y\right)\)
\(=\left(x+y\right)^3-\left(x+y\right)\)
\(=\left(x+y\right)\left[\left(x+y\right)^2-1\right]\)
\(=\left(x+y\right)\left(x+y-1\right)\left(x+y+1\right)\)
c) \(5x^2-10xy+5y^2-20z^2\)
\(=5\left(x^2-2xy+y^2-4z^2\right)\)
\(=5\left[\left(x-y\right)^2-\left(2z\right)^2\right]\)
\(=5\left(x-y-2z\right)\left(x-y+2z\right)\)
\(P=\left(x-y\right)^2+\left(x+y\right)^2-2\left(x+y\right)\left(x-y\right)-4x^2=\left(x-y-x-y\right)^2-\left(2x\right)^2=\left(-2y\right)^2-\left(2x\right)^2\)
\(=\left(2y-2x\right)\left(2y+2x\right)=2\left(y-x\right)2\left(y+x\right)=4\left(x+y\right)\left(y-x\right)\)
\(x^3-x^2y+3x-3y=x^2\left(x-y\right)+3\left(x-y\right)=\left(x-y\right)\left(x^2+3\right)\)
\(x^3-2x^2-4xy^2+x=x\left(x^2-2x+1-4y^2\right)=x\left[\left(x-1\right)^2-\left(2y\right)^2\right]=x\left(x+2y-1\right)\left(x-2y-1\right)\)
\(\left(x+2\right)\left(x+3\right)\left(x+4\right)\left(x+5\right)-8=\left(x^2+7x+10\right)\left(x^2+7x+12\right)-8\)
Đặt \(x^2+7x+10=t\), ta có:
\(t\left(t+2\right)-8=t^2+2t-8=t^2-2t+4t-8=t\left(t-2\right)+4\left(t-2\right)=\left(t-2\right)\left(t+4\right)\)
\(=\left(x^2+7x+10+4\right)\left(x^2+7x+10-2\right)=\left(x^2+7x+14\right)\left(x^2+7x-8\right)\)
3x^2 + 5y - 3xy - 5x
= 3x^2 - 3xy + 5y- 5x
= 3x ( x-y) +5( y-x)
=3x(x-y)- 5( x-y)
= (x-y)(3x-5)
3x^2 + 5y ‐ 3xy ‐ 5x = 3x^2 ‐ 3xy + 5y‐ 5x = 3x ﴾ x‐y﴿ +5﴾ y‐x﴿ =3x﴾x‐y﴿‐ 5﴾ x‐y﴿ = ﴾x‐y﴿﴾3x‐5﴿
a: \(=-2x^2y-\dfrac{5}{4}x^2y^2-\dfrac{4}{3}xy^4\)
b: \(=4x^{n-1+n+1}-6x^{n-1+1}=4x^{2n}-6x^n\)
\(=3xy\left(x-y\right)-5\left(x-y\right)=\left(x-y\right)\left(3xy-5\right)\)